Treated Pierre Robin Sequence Using Placed Allogenic Acellular Bone Matrix and Mandibular Distraction Osteogenesis in the Neonate - Han, Tao; Ji, Yi; Cui, Jie; Kong, Liangliang; Shi, Lijun; Chen, Jianbin; Shen, Weimin (Frontiers in Pediatrics, 2022)
Objective: This study aimed to report our experience with placed allogenic acellular bone matrix and mandibular distraction osteogenesis in Pierre Robin sequence (PRS), and explore the role of distraction in the osteogenesis of acellular bone. Materials and Methods: A total of 428 neonates with severe PRS managed with placing allogenic acellular bone and bilateral mandibular distraction osteogenesis were included in the study. The procedure included using oblique-shaped osteotomy, fixing bilateral mandibular distractor, instantly extending a 4-6mm gap, and placing allogenic acellular bone into the gap. The length of allogenic acellular bone was 4-5mm. Although the surgical techniques, distraction and consolidation periods were similar, the allogenic acellular bone matrix we placed was quite different from the traditional distraction. With the technology we used, tracheal intubation could be immediately removed, thus quickly improving breathing conditions compared to traditional methods after the surgery. The jaw extending and oral feeding could begin on the fifth day. The jaw was extended 0.6mm twice a day until the mandible was overcorrected by 20%. Results: All 428 cases included in this study were successfully extubated after the operation, and the difficulty in breathing was instantly relieved. Total mandibular distraction was 15 mm to 20mm. Oral feeding was started at six hours to six days postoperatively, while hospital stay ranged from 18 to 20 days postoperatively. No major complications were reported. Medium to long-term results was good. Mandibular distractors were removed after 3 months. Conclusions: Bilateral mandibular distraction osteogenesis combined with placing allogenic acellular bone in the neonate are safe and accurate procedures, which are the primary treatment options for cases of severe PRS. It can be considered that the tension of distraction can promote osteogenesis in acellular bone and thus improve distractive effect of the mandible.